2014
DOI: 10.1016/j.canlet.2014.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Wnt inhibitory factor-1 functions as a tumor suppressor through modulating Wnt/β-catenin signaling in neuroblastoma

Abstract: Neuroblastoma is the most common extracranial solid tumor in childhood and is associated with serious morbidity and mortality. The effective treatment of neuroblastoma remains one of the major challenges in pediatric oncology. The Wnt signaling pathway has been shown to play a significant role in the pathogenesis of adult and pediatric tumors. WIF-1 has been identified as an important Wnt antagonist which inhibits Wnt/β-catenin signaling by directly binding to Wnt proteins. However, the expression and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 45 publications
(60 reference statements)
2
25
0
Order By: Relevance
“…The general opposite control has been considered to be mediated by Wnt antagonists such as endogenic DKK-1, SFRP-1 and Wif-1. The main inhibitory mechanism is the interference of the combination between Wnt and its receptors (14,(30)(31)(32)(33). Fig.…”
Section: The Level Of Dkk-1 and Sfrp-1 Inversely Regulate The Inos Anmentioning
confidence: 99%
“…The general opposite control has been considered to be mediated by Wnt antagonists such as endogenic DKK-1, SFRP-1 and Wif-1. The main inhibitory mechanism is the interference of the combination between Wnt and its receptors (14,(30)(31)(32)(33). Fig.…”
Section: The Level Of Dkk-1 and Sfrp-1 Inversely Regulate The Inos Anmentioning
confidence: 99%
“…Histone modification and promoter CpG methylation alter cancer-related gene expression and are frequently involved in carcinogenesis [58] . So far, downregulation of Wnt antagonist genes associated to promoter hypermethylation have been identified in a variety of malignancies, such as renal, bladder, lung, breast, colorectal, gastric and neuroblastoma [59][60][61][62][63][64][65] . Furthermore, the Wnt/b-catenin pathway genes are found among those affected by dysregulation of microRNAs (miRNAs) in many kinds of cancers, and particularly, expression profiling has shown that certain miRNAs are associated with gastric cancer development, progression and response to therapy [66][67][68] .…”
mentioning
confidence: 99%
“…The WNT/β-catenin signaling pathway has been implicated in oncogenesis and in several developmental processes, including regulation of cell fate and patterning during embryogenesis [31]. This pathway supports stem and cancer stem cells [32].…”
Section: Discussionmentioning
confidence: 99%